2018
DOI: 10.22159/ajpcr.2018.v11i1.18330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxidative Stress Markers Malondialdehyde, Glutathione, Nitric Oxide, and Prorenin Level in Preeclampsia Placental Tissues

Abstract: Background: Preeclampsia was a syndrome of hypertension proteinuria in pregnant women. In failure of pseudo vasculogenesis, there is persistency of endothelial and smooth muscle cell of vessel wall in spiral artery. Spiral artery could not be emphasis and lead to relative hypoxia, and oxidative stress in placental tissues. Endothelial cell has property to produce nitric oxide (NO) that can dilated vessel. Placenta also produces prorenin, to maintain vascular wall tonicity. Therefore, we want to uncover the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Multiple recent studies supported our research findings, either they performed in plasma or erythrocyte; both samples showed decreased GSH level in pregnancy-induced hypertensive groups compared to the normotensive group 14,20 . However, some researchers came up with different results and observed no difference in the level of GSH in a PE and standard group in the same direction, no significant difference in the level of GSH in erythrocyte sample of severe and mild PE female than normal pregnant female 16,21 . Previously a substantially high level of GSH in placental and decidual tissues found in the PE group than normotensive 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Multiple recent studies supported our research findings, either they performed in plasma or erythrocyte; both samples showed decreased GSH level in pregnancy-induced hypertensive groups compared to the normotensive group 14,20 . However, some researchers came up with different results and observed no difference in the level of GSH in a PE and standard group in the same direction, no significant difference in the level of GSH in erythrocyte sample of severe and mild PE female than normal pregnant female 16,21 . Previously a substantially high level of GSH in placental and decidual tissues found in the PE group than normotensive 15 .…”
Section: Discussionmentioning
confidence: 97%
“…It is caused by high ROS synthesis due to active metabolism in mitochondria [18]. The opposite result is shown by Prijanti et al that showed a decrease of MDA levels in preeclampsia placental samples [12].…”
Section: Discussionmentioning
confidence: 92%
“…Sahay et al showed that MDA levels in preeclamptic placentas were higher than normal placentas, implying that ROS increase in the preeclamptic placenta [11]. In contrast, Prijanti et al showed that the MDA levels of preeclamptic placentas were lower than those of the normal placenta [12]. Nonetheless, both studies were conducted on preeclamptic placentas.…”
Section: Introductionmentioning
confidence: 99%
“…After that, 400 μL of 0.67% thiobarbituric acid (TBA) was added to the supernatant and heated at 96°C for 10 minutes. After cooling to room temperature, the absorbance was measured at 530 nm using a spectrophotometer [9].…”
Section: Mda Concentration Measurementmentioning
confidence: 99%
“…Then, as much as 1750 μL phosphate buffer and 25 μL DNTB were added into the supernatant, and was incubated in the dark place at room temperature for 1 hour. After that, the absorbance was measured at 412 nm using a spectrophotometer [9].…”
Section: Gsh Concentration Measurementmentioning
confidence: 99%